Utilizing echocardiography to monitor heartworm treatment with melarsomine: A clinical evaluation in a dog - Susilo, Anton; Devina, Yovita; Hemagiri, Theo; Hemagiri, Theo; Ismawati, Resma (ARSHI Veterinary Letters, 2024)
Dirofilariasis is a parasitic disease caused by nematodes in the blood vessels and heart. Echocardiography serves as a diagnostic test to confirm the presence of these worms and assists in staging the disease to determine an appropriate treatment protocol. This case study explored the monitoring of dirofilariasis therapy using cardiac ultrasonography. The results from the case study showed that no adult worms were detectable within the cardiac chambers 19 days after melarsomine treatment, highlighting the efficacy of this therapeutic approach in resolving heartworm infections.